1999
DOI: 10.1038/sj.bjc.6690389
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of uPA and p53 accumulation measured by quantitative biochemical assays in 1245 primary breast cancer patients: a multicentre study

Abstract: SummaryThe purpose of this retrospective multicentre study was to assess the prognostic value of urokinase plasminogen activator (uPA) and p53 levels in a large series of primary breast cancer, using an automatic quantitative luminometric method. Samples of 1245 operable breast tumours were collected from seven French institutions and patients were followed for a median of 75 months. The median uPA and p53 levels assayed in cytosols by means of the immunoluminometric technique (LIA) were 0.31 and 0.20 ng mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…In particular, in multiple studies, it has been found to be a marker of aggressiveness in node-negative patients (Table II). In this subgroup of patients, as with total populations, the prognostic impact of uPA is generally found to be independent of tumor size, grade, patient age, ER status, and progesterone receptor (PR) status [22,24,36]. In addition to the node-negative subgroup, uPA levels have been shown to correlate with patient outcome in node-positive, premenopausal, postmenopausal, and ER-positive subgroups [35].…”
Section: Breast Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, in multiple studies, it has been found to be a marker of aggressiveness in node-negative patients (Table II). In this subgroup of patients, as with total populations, the prognostic impact of uPA is generally found to be independent of tumor size, grade, patient age, ER status, and progesterone receptor (PR) status [22,24,36]. In addition to the node-negative subgroup, uPA levels have been shown to correlate with patient outcome in node-positive, premenopausal, postmenopausal, and ER-positive subgroups [35].…”
Section: Breast Cancermentioning
confidence: 98%
“…As an indicator of patient outcome, most investigators find that the prognostic impact of uPA is independent of traditionally used markers such as axillary node status, tumor size, tumor grade, and estrogen receptor (ER) status [15,24,32,33]. In most studies with short-term followup, uPA is a more potent predictor of disease-free and overall survival than either tumor size or ER status and of similar strength to nodal status [32,33].…”
Section: Breast Cancermentioning
confidence: 99%
“…This decrease in uPA and PAI-1 production in ER-positive tumors has previously been reported. 18,32,33 At the gene level, a non-aggressive phenotype has been identified in cells exhibiting ER-positive expression and a lack of PAI-1 expression, whereas inversely, cells devoid of ER expression but positive for PAI-1 were shown to be invasive. 34 A potentially more aggressive subgroup of highly ER-positive BC might be in keeping with some previous observations of Thorpe and colleagues, who showed that the natural history of tumors with high ER levels is more deleterious.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Elaboration of these molecules influences two major features associated with lung neoplasia, including excessive proliferation of neoplastic cells and their capacity to invade normal tissues. It is now clear that the pathogenesis of lung neoplasia prominently involves expression of tumor suppressor protein p53 (22)(23)(24) as well as extracellular matrix degradation by uPA-mediated plasminogen activation (6,7,24). Among the plethora of potentially useful markers of tumor virulence that have been identified to date, both uPA and p53 appear to be promising (24,25).…”
mentioning
confidence: 99%